Characterization of the protease activity in the chemotactic factor inactivator. - Ward, P A (1976)
The chemotactic factor inactivator (CFI) isolated from human serum contains a kininase activity that causes extensive hydrolysis of bradykinin. The highly chemotactic synthetic peptide Met-Leu-Phe was completely hydrolyzed by CFI preparations. The release of the constituent amino acids from this peptide coincided with a loss of its chemotactic activity. The N-formyl, but not the amide derivative, of the leukotactic peptide Met-Leu-Phe was resistant to the action of CFI, as evidenced by chemotactic and biochemical assays. Examination of the specificity of CFI proteolysis revealed that short polypeptide substrates are degraded sequentially from the amino terminus. Larger peptides are less extensively hydrolyzed, and the patterns of hydrolysis are more complex. Inactivation of the bacterial chemotactic factors by CFI was overcome by the addition of high concentrations of peptides which were substrated for CFI. CFI preparations readily hydrolyzed the peptide Arg-Phe-Ala. The constituent amino acids were conveniently identified by thin-layer chromatography method. This procedure afforded a rapid assay for measuring CFI activity in the whole human serum as well as in fractions throughout the purification steps. Moreover, CFI also hydrolyzed L-leucyl-beta-napthylamide at rates comparable to peptides. Thus, L-leucyl-beta-napthylamide served as a useful substrate for estimating CFI activity in preparations at various stages of purification. This substrate was also useful in kinetic studies. The results from these studies indicate an aminopeptidase activity is the mechanism whereby CFI inhibits the activity of chemotactic substrates.